2017
DOI: 10.1371/journal.pone.0169522
|View full text |Cite
|
Sign up to set email alerts
|

Salmon DNA Accelerates Bone Regeneration by Inducing Osteoblast Migration

Abstract: The initial step of bone regeneration requires the migration of osteogenic cells to defective sites. Our previous studies suggest that a salmon DNA-based scaffold can promote the bone regeneration of calvarial defects in rats. We speculate that the salmon DNA may possess osteoinductive properties, including the homing of migrating osteogenic cells. In the present study, we investigated the influence of the salmon DNA on osteoblastic differentiation and induction of osteoblast migration using MG63 cells (human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…We previously reported that 300 bp DNA/protamine scaffolds disappear early after implantation into rat calvarial bone defects . We also showed that high molecular weight DNA, as used in the present experiments, promotes new bone formation by attracting osteoblasts . The addition of DNA to preosteoblast cultures promotes osteogenic differentiation and cellular migration in vitro .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We previously reported that 300 bp DNA/protamine scaffolds disappear early after implantation into rat calvarial bone defects . We also showed that high molecular weight DNA, as used in the present experiments, promotes new bone formation by attracting osteoblasts . The addition of DNA to preosteoblast cultures promotes osteogenic differentiation and cellular migration in vitro .…”
Section: Discussionsupporting
confidence: 74%
“…Some reports have indicated that extracellular phosphate promotes osteogenic differentiation and calcification of preosteoblasts and mesenchymal stem cells . Furthermore, we have recently shown that the DNA itself enhances osteogenesis by increasing phosphate transporter activity and cell migration, resulting in new bone formation in a calvarial defect model.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, enhanced staining with ALP was observed in spheroid-derived HPLSCs cultured with OIM. Similarly, spheroid-derived HPLSCs cultured with OIM showed increased expression levels of Runx2 and osterix, which are known markers of the early stage of osteogenesis 27,30,31) , by western blot analysis. These findings indicate that, as compared with monolayer-derived HPLSCs, HPLSC spheroids are more susceptible to osteogenic differentiation, resulting in accelerated osteogenic differentiation in the early stage.…”
Section: Discussionmentioning
confidence: 93%